Changes to Antiretroviral Drug Regimens during Integrated TB–HIV Treatment: Results of the Sapit Trial. Issue 2 (February 2014) - Naidoo, Anushka; Naidoo, Kogieleum; Yende-Zuma, Nonhlanhla; Gengiah, Tanuja N; Padayatchi, Nesri; Gray, Andrew L; Bamber, Sheila; Nair, Gonasagrie; Karim, Salim S Abdool
Background: Frequency of drug changes in combination antiretroviral therapy among patients starting both tuberculosis (TB) and HIV therapy, as a result of treatment-limiting toxicity or virological failure, is not well established. Methods: Patients in the Starting Antiretroviral Therapy at Three Points in Tuberculosis (SAPiT) trial were randomized to initiate antiretroviral therapy (ART) either early or late during TB treatment or after completion of TB treatment. Drug changes due to toxicity (defined as due to grade 3 or 4 adverse events) or virological failure (defined as viral load >1, 000 copies/ml on two occasions, taken ≥4 weeks apart) were assessed in these patients. Results: A total of 501 TB–HIV-coinfected patients were followed for a mean of 16.0 months (95% CI 15.5, 16.6) after ART initiation. The standard first-line antiretrovirals used were efavirenz, lamivudine and didanosine. Individual drug switches for toxicity occurred in 14 patients (incidence rate 2.1 per 100 person-years, 95% CI 1.1, 3.5), and complete regimen changes due to virological failure in 25 patients (incidence rate 3.7 per 100 person-years, 95% CI 2.4, 5.5). The most common treatment limiting toxicities were neuropsychiatric effects ( n =4, 0.8%), elevated transaminase levels and hyperlactataemia ( n =3, 0.6%), and peripheral neuropathy ( n =2, 0.4%). Complete regimen change due to treatment failure was more common in patients with CD4 + T-cell count <50 cells/mm 3 ( P <0.001) at ART initiation and body mass index >25 kg/m 2 ( P =0.01) at entry into the study. Conclusions: Both drug switches and complete regimen change were uncommon in patients cotreated for TB–HIV with the chosen regimen. Patients with severe immunosuppression need to be monitored carefully, as they were most at risk for treatment failure requiring regimen change.